VD_FINDINFO Décision / 2013 / 663 vom 18. Juli 2013 - VD Tribunal cantonal (2013)
DÉFENSE D'OFFICE, ASSISTANCE JUDICIAIRE | 132 al. 1 let. b CPP (CH), 132 al. 2 CPP (CH), 132 CPP (CH), 136 CPP (CH), 393 al. 1 let. a CPP (CH)